2022
DOI: 10.3389/fimmu.2022.971866
|View full text |Cite
|
Sign up to set email alerts
|

Complement-mediated serum bactericidal activity of antibodies elicited by the Shigella sonnei GMMA vaccine in adults from a shigellosis-endemic country: Exploratory analysis of a Phase 2a randomized study

Abstract: Shigella is associated with a significant burden of disease worldwide among individuals of all ages and is the major cause of moderate and severe diarrhea in children under five years of age in low- and middle-income countries. Several candidate vaccines against Shigella species are currently under clinical development. The investigational 1790GAHB vaccine against Shigella sonnei is based on GMMA (Generalized Modules for Membrane Antigens) technology. The vaccine was well tolerated and induced high antibody le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…These vaccines have been proven to be immunogenic and efficacious in animal models (Micoli et al, 2018;Gasperini et al, 2021). Similar approaches are being used for the development of novel vaccines against Shigella, where GMMA from bacteria with msbB or htrB deletions (Rossi et al, 2014;Gerke et al, 2015) were safe (Launay et al, 2017;Obiero et al, 2017) and able to elicit functional antibodies in humans (Micoli et al, 2021;Kapulu et al, 2022). Other examples of bacterial vaccines based on this strategy are those against Neisseria meningitidis, with pentacylated LPS obtained via deletion of lpxL1, which have been tested preclinically (Koeberling et al, 2014) and clinically (Keiser et al, 2011).…”
mentioning
confidence: 99%
“…These vaccines have been proven to be immunogenic and efficacious in animal models (Micoli et al, 2018;Gasperini et al, 2021). Similar approaches are being used for the development of novel vaccines against Shigella, where GMMA from bacteria with msbB or htrB deletions (Rossi et al, 2014;Gerke et al, 2015) were safe (Launay et al, 2017;Obiero et al, 2017) and able to elicit functional antibodies in humans (Micoli et al, 2021;Kapulu et al, 2022). Other examples of bacterial vaccines based on this strategy are those against Neisseria meningitidis, with pentacylated LPS obtained via deletion of lpxL1, which have been tested preclinically (Koeberling et al, 2014) and clinically (Keiser et al, 2011).…”
mentioning
confidence: 99%
“…39 Interestingly, in the same study, when assessing correlation with other immunomarkers, bactericidal activity showed the strongest correlation with α4β7+ IgG responses, followed by serum IgG1 responses. 39 We also previously reported a strong correlation between the 1790GAHB elicited SBA titers and anti-S. sonnei LPS serum IgG levels in adults from both Shigella-endemic 29 and non-endemic countries, 18 indicating the functionality of antibodies induced by vaccination. The magnitude of antibody responses may play a less signi cant role in protection than their functionality; for instance, ndings from a CHIM study suggest that Shigella-speci c serum IgG1 may play an important role in protection from shigellosis after parenteral immunization even at relatively low levels elicited post-vaccination, 39 due to their high e ciency in activating the complement cascade.…”
Section: Discussionmentioning
confidence: 69%
“…38 Interestingly, in the same study, when assessing correlation with other immunomarkers, bactericidal activity showed the strongest correlation with α4β7 + IgG responses, followed by serum IgG1 responses. 38 We also previously reported a strong correlation between the 1790GAHB elicited SBA titers and anti-S. sonnei LPS serum IgG levels in adults from both Shigella-endemic 29 and non-endemic countries, 18 indicating the functionality of antibodies induced by vaccination. The magnitude of antibody responses may play a less signi cant role in protection than their functionality; for instance, ndings from a CHIM study suggest that Shigellaspeci c serum IgG1 may play an important role in protection from shigellosis after parenteral immunization even at relatively low levels elicited post-vaccination, 38 due to their high e ciency in activating the complement cascade.…”
Section: Discussionmentioning
confidence: 81%
“…18,30,31 Moreover, serum IgG antibodies were bactericidal and 1790GAHB showed ability to boost the response in individuals preimmunized or naturally exposed to Shigella. 29,32 While the vaccine did not show clinical e cacy against shigellosis after challenge with S. sonnei in this CHIM trial, 33 the study design allowed us to explore the role of several immunomarkers in predicting the risk of shigellosis.…”
Section: Discussionmentioning
confidence: 92%